Site characteristics determine the effectiveness of tillage and cover crops on the net ecosystem carbon balance in California vineyard agroecosystems - Zumkeller, Maria; Yu, Runze; Torres, Nazareth; Marigliano, Lauren E.; Zaccaria, Daniele; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2022)
Globally wine grape vineyards cover approximately 7.4 M ha. The potential for carbon (C) storage in vineyards is of great interest to offset greenhouse gas emissions and mitigate the effects of climate change. Sustainable soil management practices such as cover crop adoption and reduced tillage may contribute to soil organic carbon (SOC) sequestration. However, site specific factors such as soil texture, other soil physicochemical properties, and climate largely influence the range and rate to which SOC may be stored. To measure the potential for C storage in vineyards under varying sustainable soil management practices, we calculated net ecosystem carbon balance (NECB) of three cover crops (Perennial grass (Poa bulbosa hybrid cv. Oakville Blue); Annual grass (Barley, Hordeum vulgare); Resident vegetation (natural weed population) under conventional tillage (CT) and no-till (NT) management. Results provided evidence that vineyards served as C sinks. In sandy soils, the type of cover crop and tillage may be of little influence on NECB. While in finer textured soils, tillage reduced NECB and higher biomass producing cover crops enhanced the overall C storage potential of the vineyard agroecosystem. Overall, our results revealed that site characteristics, namely soil texture and climate, were key determinants of the C storage potential of vineyards in Mediterranean climates such as those found in coastal and inland California wine grape production regions. Keywords: climate change; carbon sequestration; cover crop; tillage; soil conservation